Highly Selective Artificial Cholesteryl Crown Ether K+‐Channels. Issue 48 (6th October 2015) - Sun, Zhanhu; Barboiu, Mihail; Legrand, Yves‐Marie; Petit, Eddy; Rotaru, Alexandru
Abstract: The bacterial KcsA channel conducts K + cations at high rates while excluding Na + cations. Herein, we report an artificial ion‐channel formed by H‐bonded stacks of crown‐ethers, where K + cation conduction is highly preferred to Na + cations. The macrocycles aligned along the central pore surround the K + cations in a similar manner to the water around the hydrated cation, compensating for the energetic cost of their dehydration. In contrast, the Na + cation does not fit the macrocyclic binding sites, so its dehydration is not completely compensated. The present highly K + ‐selective macrocyclic channel may be regarded as a biomimetic of the KcsA channel. Abstract : Crown ether ion channels : High selectivity for K + translocation through the artificial macrocycle channels is reminiscent of the conductance states of natural KcsA channels. It relates to the macrocycles binding ability surrounding the K + cations in a similar manner to the water molecules around the hydrated cation in water.